一种频段、带宽可调的差分收发信机 (2023)
为克服现有技术中的不足，本发明提出了一种具有可以灵活调整链路中滤波器工作频段和带宽的差分收发信机，来提升对不同中心频率和带宽的无线信号的高性能接收。其中该滤波器电路结构是差分带通滤波器结构，具有对带宽和频段在其最大变化范围内任意重构改变的功能，将该差分滤波器结构应用到收发信机中时，能够有效消除混频器在变频过程中可能引入空间和电路回路中的杂散信号。从而降低了带内不期望的互调杂散信号，提高了系统的动态范围和信噪比。该电路结构可以同时实现对带宽和频段在其最大变化范围内任意重构改变。差分带通滤波器结构有两个主要部分，即差分谐振反相器和一个差分并联谐振器。 In order to overcome the defects in the prior art, the invention provides a differential transceiver capable of flexibly adjusting the working frequency band and bandwidth of a filter in a link so as to improve the high-performance reception of wireless signals with different center frequencies and bandwidths. The filter circuit structure is a differential band-pass filter structure and has the function of randomly reconstructing and changing the bandwidth and the frequency band within the maximum change range, and when the differential filter structure is applied to a transceiver, spurious signals possibly introduced into a space and a circuit loop in the frequency conversion process of a frequency mixer can be effectively eliminated. T